Simple Method to Measure the Aerodynamic Size Distribution of Porous Particles Generated on Lyophilizate for Dry Powder Inhalation - Kahori Miyamoto; Hiroaki Taga; Tomomi Akita; Chikamasa Yamashita (MDPI AG, 2020)
Recently, statistical techniques such as design of experiments are being applied for efficient optimization of oral formulations. To use these statistical techniques for inhalation formulations, efficient methods for rapid determination of the aerodynamic particle size distribution of many samples are needed. Therefore, we aimed to develop a simple method to measure aerodynamic particle size distribution that closely agrees with the results of inhalation characteristic tests. We added attachments for dispersion to the aerodynamic particle sizer (APS) so that formulations could be dispersed under the same condition as for multi-stage liquid impinger (MSLI) measurement. Then, we examined the correlation between MSLI and APS using lyophilizate for dry powder inhalation formulations that generate porous particles just on inhalation. It is difficult to obtain the accurate aerodynamic particle size distribution of porous particles by APS because the particle density is difficult to estimate accurately. However, there was a significant correlation between MSLI and APS when the particle density settings for APS measurement was calculated by a conversion factor based on the result of MSLI. The APS with dispersion attachments and this conversion factor can measure a number of samples in a short time, thereby enabling more efficient optimization of dry powder inhalers.